Praktik Lapang Tematik (PLT): Bermain Pianika Tangga Nada Dasar Bagi Siswa Sekolah Dasar di Lingkungan 2 Binjai Timur - Ance Panggabean; Elvita Uli Purba; Varican Malau (LPPM Universitas HKBP Nommensen, 2022)
Thematic Field Practice (Praktek lapang tematik/PLT) has become part of the implementation of learning activities for students, especially in the Music Arts Study Program at HKBP Nommensen University. This practice provides an opportunity for students to apply the abbilities or learning possessed by students to be applied to the community. Selesction of the PLT competency field in understanding basic music theory, making students a problem solver for students in elementary school in Lingkungan 2 Dataran Tinggi Binjai Timur. The problems found in elementary school students who still do not understand the basic techniques of playing the piano using basic music theory, namely scales as a learnig references. PLT has a positive influence on the development of students skills in playing the piano using basic scale.